NUEVAS MICROFLORAS DE LA FORMACION LAGARES (CARBONIFERO), PROVINCIA DE LA RIOJA, REPUBLICA ARGENTINA (Ameghiniana, 2013)
New palynological samples from the Lagares Formation at the localities of Mine La Margarita and Los Mogotes Colorados, show interesting associations which are described. Two new species are established: Lophotriletes discordis and Portalites baculus. The following species are recorded for the first time in this lithostratigraphical the unit: Horriditrlletes uruguaiensis (Marques Toigo) Archangelsky & Gamerro, Punctatisporlies lucidulus Playford & Helby, Raistrickia radiosa Playford & Helby, Foveosporites pellucidus Playford & Helby and Lundbladispora irregularis (Menéndez) Césari.